A high-rate and ultrastable anode enabled by boron-doped nanoporous carbon spheres for high-power and long life lithium ion capacitors. (September 2018) - Sun, Fei; Wu, Hao Bin; Liu, Xin; Liu, Fang; Han, Rui; Qu, Zhibin; Pi, Xinxin; Wang, Lijie; Gao, Jihui; Lu, Yunfeng
Abstract: Lithium ion capacitors (LICs) hold potentials to bridge the gap between lithium ion batteries and supercapacitors; however, the imbalance of electrochemical kinetic and stability between Li + storage anode and capacitive cathode has been the key bottleneck. Herein, we report a high-rate and ultrastable anode for this issue, consisting of boron-doped nanoporous carbon spheres which are synthesized by a continuous spraying-assisted co-assembly process. Experimental and computational investigations as well as the comparison with a nitrogen-rich carbon indicate that boron species enhances ion-surface interactions, electron/ion conductivity and carbon framework cycling firmness, leading to dramatically improved rate and cycling performances, which outperform the extensively explored nitrogen doped carbons and most reported high-rate anode materials. By pairing a coal-derived microporous graphene cathode, we constructed a full-carbon LIC device exhibiting high energy and power densities (207 Wh kg −1 at 511 W kg −1 and still 136 Wh kg −1 at 17.06 kW kg −1 ), as well as an unprecedented cycling stability with no capacity decay after 15, 000 cycles at 2 A g −1 . This work not only offers a fundamental basis to understand the enhanced anode performance by doping boron into carbon framework but also provides an effective strategy to circumvent the kinetic and stability discrepancies between anode and cathode for high-performance LICs. Graphical abstract: Image 1 Highlights: Boron-doped carbon spheres are synthesized by a continuous spraying process. Boron decoration greatly enhances carbon framework firmness. Boron doping circumvents charge storage discrepancies between anode and cathode. Computational investigations are conducted to reveal the boron doping effects.